2021
DOI: 10.3389/fmicb.2021.619970
|View full text |Cite
|
Sign up to set email alerts
|

Xylanase Supplementation Modulates the Microbiota of the Large Intestine of Pigs Fed Corn-Based Fiber by Means of a Stimbiotic Mechanism of Action

Abstract: This research tested the hypothesis that xylanase modulates microbial communities within the large intestine of growing pigs fed corn-based fiber through a stimbiotic mechanism(s) of action (MOA). Sixty gilts were blocked by initial body weight, individually housed, and randomly assigned to one of four dietary treatments (n = 15): a low-fiber (LF) control, a high-fiber (HF) control containing 30% corn bran, HF+100 mg/kg xylanase (HF+XY), and HF+50 mg/kg arabinoxylan-oligosaccharide (HF+AX). Pigs were fed dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Xylanase is a carbohydrase that hydrolyzes the β-(1–4) glycosidic bonds of arabinoxylans, and thus, has the potential to partially reduce the anti-nutritive effects of dietary fibre [ 16 ]. Xylo-oligosaccharides (XOS) produced by exogenous xylanase (EX) acts either directly as a prebiotic or a signalling molecule to stimulate fibre-degrading microbiota and cross-feeding mechanisms [ 17 ]. However, a broiler study reported that the amount of XOS generated by EX is somewhat dependent on the structure of the fibre in the basal diet and often is not sufficient to explain the increased butyrate and other short-chain fatty acids (SCFA) in the caeca [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xylanase is a carbohydrase that hydrolyzes the β-(1–4) glycosidic bonds of arabinoxylans, and thus, has the potential to partially reduce the anti-nutritive effects of dietary fibre [ 16 ]. Xylo-oligosaccharides (XOS) produced by exogenous xylanase (EX) acts either directly as a prebiotic or a signalling molecule to stimulate fibre-degrading microbiota and cross-feeding mechanisms [ 17 ]. However, a broiler study reported that the amount of XOS generated by EX is somewhat dependent on the structure of the fibre in the basal diet and often is not sufficient to explain the increased butyrate and other short-chain fatty acids (SCFA) in the caeca [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ribeiro et al [ 19 ] stated that a small level of XOS is more likely to perform as an activator of specific bacteria in the gastrointestinal tract (GIT) than directly act as a quantitative prebiotic. The stimbiotic (STB) concept has been recently introduced as a non-digestible and fermentable additive that stimulates the development of a proportion of the microbiome comprising bacterial species that are principally involved in fibre degradation [ 17 , 20 ]. It was reported that a low concentration of STB induced a better fermentation activity in the colonic samples compared with 10–20 times higher doses of commercially available prebiotics.…”
Section: Introductionmentioning
confidence: 99%
“…However, benefits of xylanase on growth performance of broilers supplemented non-viscous corn-based diets also were recorded ( Khadem et al, 2016 ). Xylanase can reduce chyme viscosity, release nutrients from inside cell wall, and xylo-oligosaccharides (XOS) as a result of AX degradation in the gastrointestinal tract (GIT), which may then act like a prebiotic ( Gonzalez-Ortiz et al, 2017 ; Petry et al, 2021 ). Previous studies have demonstrated that the dominant mode of action responsible for benefits of xylanase in corn- or wheat-based diets may be distinct and impacts of xylanase on growth performance, nutrient utilization, digesta characteristics, and cecal volatile fatty acid (VFA) concentrations of broilers fed corn- or wheat-based diets were compared ( Kiarie et al, 2014 ; Munyaka et al, 2016 ; McCafferty et al, 2019a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…The xylanase is generally considered to work through two stages, namely, an ileal stage and a cecal stage (Engberg et al, 2004). Most studies focused on effects of xylanase on cecal microbiota; the knowledge regarding ileal microbiota was limited (McCafferty et al, 2019a,b;Petry et al, 2021). In fact, NSP-degrading enzyme improves small intestine digestion as a consequence decreases undigested substrates in the small intestine, which might also result in the reduction of fermentative microorganisms and potentially pathogenic microorganisms in the ileum (Danicke et al, 1999;Raza et al, 2019).…”
Section: Introductionmentioning
confidence: 99%